Dietary Inclusion Rate of Cocoa Husk for Starter Cockerels - Olubamiwa, O.; A.R., Otun; Longe, O.G. (International Journal of Poultry Science, 2002)
Growth performance and economics of production were measured to assess the dietary inclusion rate of cocoa husk for starter cockerels. The study involved 156, 2-week-old cockerels which were reared for 6 weeks on four diets incorporating 0, 10, 15 and 20% cocoa husk meal (CHM) at the expense of maize. Body weight gain and feed conversion were depressed beyond the 10% CHM level. Although cost of feed consumed decreased across treatments, feed cost/kg body weight gain was reduced beyond the 10% CHM level. Ten percent dietary inclusion of CHM appears optimal in cockerel starter diets since beyond this level, growth performance and monetary gains are sacrificed.